Multiarea Economic-Emission Dispatch Using Simplex Based Particle Swarm Optimization Method - Chopra, Namarta; Brar, Y. S.; Dhillon, J. S. (Asian Journal of Electrical Sciences, 2018)
This paper introduces the hybridization of Particle Swarm Optimization (PSO) with Simplex Search Method (SSM) in the field of Multi Area Power Dispatch (MAPD) problem. The proposed simplex based particle swarm optimization (SPSO) helps in refining the global solution obtained using PSO, with local search through SSM. As in today’s power industry, the energy flow between the areas and fossil fuel emissions from the generating units are of major concern. So, the objective of MAPD is to reduce the overall generation cost of the areas along with the reduction of pollutants’ emissions also. The comparison with Single Area Power Dispatch (SAPD) system is done to understand the benefit of resolving the whole region into small areas. Due to the conflicting nature of both the objectives, Price Penalty Factor (PPF) method is used to convert the multiobjective problem into single objective optimization problem while satisfying its various equality and inequality constraints. The effectiveness of the proposed method is tested on a test system consisting four areas, twelve generator system under both MAPD and SAPD cases. These cases are compared with each other and with the available literature to show the robustness of the proposed method.